EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PPH NON MIGAS DAN PPN TERHADAP PENERIMAAN PAJAK TAHUN 2011 – 2013 (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA SURABAYA RUNGKUT) - RAHMAYANTI, FETTY NUR (Jurnal Mahasiswa Perpajakan, 2015)
Non-oil and Gas Tax receipts and VAT is the largest contributor of tax revenue sector under the respective working areas in KPP Pratama Surabaya Rungkut. The purpose of this research is to know the tax receipts from Non-oil and Gas Tax receipts and VAT in KPP Pratama Surabaya Rungkut and as well as to know and analyze the effectiveness and contribution of the receipts of Non-oil and Gas Tax receipts and VAT in KPP Pratama Surabaya Rungkut tax revenue year 2011 – 2013. The research method used is descriptive percentage with a qualitative approach. The data used are secondary data from the period 2011 until 2013. The result of this research are for the year 2011 to 2013 level of effectiveness of Non-oil and Gas income tax receipts amounting to 83,71 percent, 92,79 percent and 78,19 percent of the target that have beeen set previously, while the Non-oil and Gas income tax revenue during the year have a pretty good contribution to total tax revenue in KPP Pratama Surabaya Rungkut. The level of effectiveness of each VAT receipts amounting to the 113,98 percent, 95,37 percent and 81,60 percent with acceptance during the year had an excellent contribution to the total tax revenue. Recommendations addressed to the relevant agencies in this case KPP Pratama Surabaya Rungkut, is in doing the targeting of non-oil revenues from income tax and VAT in order to adjust the target setting by observing the realization of the previous year received so that the effectiveness of a good reception from the non-oil income tax and VAT can improved and did not decrease the effectiveness of the reception continues - as a result of targets being set too high.Keywords : Realization of acceptance, Non-oil and Gas Tax, VAT, Effectiveness, Contributions